ChatGPT as a global doctor: a rapid review of its performance on national licensing medical examination - Flores-Cohaila, Javier A. (2025)
Objective: To evaluate ChatGPT's performance onNLMEs worldwide and determine whether it could achieve licensure to practice medicine across different countries. Methods: We searched PubMed, Scopus, andGoogle Scholarforstudies evaluating ChatGPT's performance onNLMEs. Reference lists of included studies were also reviewed. Two reviewers independently screened studies and extracted the accuracy rates(performance) of GPT-3.5 and GPT-4, including those that passed thresholds, human examinee scores, and other study characteristics. The risk of bias was assessed using the JBI Critical Appraisal Checklist for Prevalence Studies. Results: We identified 37 studies evaluating ChatGPT's performance across 18 NLMEs. Most studies assessed the United States, Chinese, and Japanese examinations. While most studies used official datasets, others relied on unofficial third-party sources, and few employed advanced prompting techniques.GPT-4 wassuperiortoGPT-3.5 in allNLMEs, with accuracy rates ranging from 67% to 89%. GPT-4 passed all 18 NLMEs (100%), while GPT-3.5 passed 10 of 15 (67%). Compared to human examinees, GPT-4 outperformed the average score in 6 of 7 NLMEs (86%); the sole exception was Japan, where examinees achieved 84.9% versus 81.5% for GPT-4. Conclusion: Current evidence demonstrates that GPT-4 can pass all 18 NLMEs evaluated, surpassing human examinees in most cases. However, this finding likely reflects low passing thresholds rather than AI superiority over physicians.